Respuesta :

Answer:

y = 3 and x = 4

Step-by-step explanation:

Let's solve your system by substitution.

6x+5y=39;3x+5y=27

Step: Solve6x+5y=39for x:

6x+5y=39

6x+5y+−5y=39+−5y(Add -5y to both sides)

6x=−5y+39

6x/6=−5y+39/6

(Divide both sides by 6)

x=−5/6y+13/2

Step: Substitute −5/6y+13/2 for x in 3x+5y=27:

3x+5y=27

3(−5/6y+13/2)+5y=27

5/2y+39/2=27(Simplify both sides of the equation)

5/2y+39/2+−39/2=27+−39/2

(Add (-39)/2 to both sides)

5/2y=15/2

5/2y/5/2=15/2/5/2

(Divide both sides by 5/2)

y=3

Step: Substitute 3 for y in x=−5/6y+13/2:

x=−5/6y+13/2

x=−5/6(3)+13/2

x=4(Simplify both sides of the equation)